(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s
(3ChdgG (B:s
(3eHJhQI GdChd, hjHOC GdehLhO efgG CKfGA JaSjQ GdBjI (B108 (3ef ShQI ghO(B: ...{(3hCeG GdPjf SYOhG aaj GdLfI(B... (3ZjQ eLPhP(B} (3ZjQ ebWhY hgh JUQjM HCf GdKhGH dG jfbWY(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG ef JaSjQ GdBjI (B117 (3ef ShQI GdeGFOI(B: { ...(3hEf JZaQ dge aEfc CfJ GdYRjR GdMcje(B} (3adG YLR(B...(3aEfc GdbGOQ Gdbhj Ydi GdKhGH hGdYbGH(B...s
(3ajgG GVWQGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B110s
(3cTa GdXfhf(B:(3L(B1(3,U(B186s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJaSjQ hYdhe GdbQBfs